2012
DOI: 10.1002/acr.21761
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of osteoporosis and fracture in women with systemic sclerosis: A comparative study with rheumatoid arthritis

Abstract: Objective. To investigate whether women with systemic sclerosis (SSc) have an increased risk of osteoporosis (OP) and related fractures compared to a high-risk population with rheumatoid arthritis (RA) and also healthy controls, and to determine putative specific OP and fracture risk factors. Methods. We performed a cross-sectional study with successive inclusion of age-matched healthy women and women with SSc and RA. Risk factors for OP and fracture were collected for all patients. Bone mineral density (BMD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
77
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 32 publications
12
77
1
8
Order By: Relevance
“…However, we believe that these results were limited by the small sample size because the rates of osteoporosis and BMD in the SSc cohort were similar to those of rheumatoid arthritis. A case–control study by Weiss et al indicated an increased risk of hip fracture in SSc patients compared with healthy controls11; this was further supported by the cross-sectional study of Avouac et al , which reported a significantly higher prevalence of OF in 71 SSc patients compared with 227 healthy controls 13. Several results of the present study are consistent with these results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, we believe that these results were limited by the small sample size because the rates of osteoporosis and BMD in the SSc cohort were similar to those of rheumatoid arthritis. A case–control study by Weiss et al indicated an increased risk of hip fracture in SSc patients compared with healthy controls11; this was further supported by the cross-sectional study of Avouac et al , which reported a significantly higher prevalence of OF in 71 SSc patients compared with 227 healthy controls 13. Several results of the present study are consistent with these results.…”
Section: Discussionsupporting
confidence: 90%
“…Up to 23–58% of the SSc patients in various studies had been exposed to glucocorticoids 13 17 19 24. We determined that a 4.75-fold fracture risk occurred in SSc patients when the daily dose was >7.5 mg of prednisolone equivalents.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported that below-normal bone mineral density (BMD) was significantly more prevalent among patients with RA patients than among those without RA (7.8 vs. 1.0 %, respectively) [16]. Similar findings have been reported in patients with other rheumatologic disorders such as systemic scleroderma [5]. Glucocorticoid administration may play a pivotal role in RA-related bone loss via several different mechanisms [25].…”
Section: Discussionmentioning
confidence: 74%
“…In particular, vitamin D deficiency is common in patients with RA, even those who regularly take supplements [21]. A low 25(OH) D level has been identified as an independent risk factor for fractures in RA [5]. However, information about individuals' use of vitamin D and calcium supplements was not available in this database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation